Phylogeny, biogeography and diversification patterns of side-necked turtles (Testudines: Pleurodira). Issue 3 (28th March 2018) - Ferreira, Gabriel S.; Bronzati, Mario; Langer, Max C.; Sterli, Juliana
Abstract : Pleurodires or side-necked turtles are today restricted to freshwater environments of South America, Africa–Madagascar and Australia, but in the past they were distributed much more broadly, being found also on Eurasia, India and North America, and marine environments. Two hypotheses were proposed to explain this distribution; in the first, vicariance would have shaped the current geographical distribution and, in the second, extinctions constrained a previously widespread distribution. Here, we aim to reconstruct pleurodiran biogeographic history and diversification patterns based on a new phylogenetic hypothesis recovered from the analysis of the largest morphological dataset yet compiled for the lineage, testing which biogeographical process prevailed during its evolutionary history. The resulting topology generally agrees with previous hypotheses of the group and shows that most diversification shifts were related to the exploration of new niches, e.g. littoral or marine radiations. In addition, as other turtles, pleurodires do not seem to have been much affected by either the Cretaceous–Palaeogene or the Eocene–Oligocene mass extinctions. The biogeographic analyses highlight the predominance of both anagenetic and cladogenetic dispersal events and support the importance of transoceanic dispersals as a more common driver of area changes than previously thought, agreeing with previous studies with other non-turtle lineages.